Differential Effects of Methyl Jasmonate on the Expression of the Early Light-Inducible Proteins and Other Light-Regulated Genes in Barley - Wierstra, Inken (American Society of Plant Physiologists, 2000)
The effects of methyl jasmonate (JA-Me) on early light-inducible protein (ELIP) expression in barley (Hordeum vulgare L. cv Apex) have been studied. Treatment of leaf segments with JA-Me induces the same symptoms as those exhibited by norflurazon bleaching, including a loss of pigments and enhanced light stress that results in increased ELIP expression under both high- and low-light conditions. The expression of both low- and high-molecular-mass ELIP families is considerably down-regulated by JA-Me at the transcript and protein levels. This repression occurs despite increased photoinhibition measurable as a massive degradation of D1 protein and a delayed recovery of photosystem II activity. In JA-Me-treated leaf segments, the decrease of the photochemical efficiency of photosystem II under high light is substantially more pronounced as compared to controls in water. The repression of ELIP expression by JA-Me is superimposed on the effect of the increased light stress that leads to enhanced ELIP expression. The fact that the reduction of ELIP transcript levels is less pronounced than those of light-harvesting complex II and small subunit of Rubisco transcripts indicates that light stress is still affecting gene expression in the presence of JA-Me. The jasmonate-induced protein transcript levels that are induced by JA-Me decline under light stress conditions.